Cocaine Experience Establishes Control of Midbrain Glutamate and Dopamine by Corticotropin-Releasing Factor: A Role in Stress-Induced Relapse to Drug Seeking - Wang, Bin (J Neurosci, 2005)
Footshock stress can reinstate cocaine-seeking behavior through a central action of the stress-associated neurohormone corticotropin-releasing factor (CRF). Here we report (1) that footshock stress releases CRF in the ventral tegmental area (VTA) of the rat brain, (2) that, in cocaine-experienced but not in cocaine-naive rats, this CRF acquires control over local glutamate release, (3) that CRF-induced glutamate release activates the mesocorticolimbic dopamine system, and (4) that, through this circuitry, footshock stress triggers relapse to drug seeking in cocaine-experienced animals. Thus, a long-lasting cocaine-induced neuroadaptation, presumably at the level of glutamate terminals in the VTA, appears to play an important role in stress-induced relapse to drug use. Similar neuroadaptations may be important for the comorbidity between addiction and other stress-related psychiatric disorders.